2009
DOI: 10.1002/cncr.24154
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of clinical evaluation of locally advanced breast cancer in patients receiving neoadjuvant chemotherapy

Abstract: Physical examination (PE), mammography (MG), breast MRI, FDG-PET and pathologic evaluation are used to assess primary breast cancer. Their accuracy has not been well studied in patients receiving neoadjuvant chemotherapy. Accuracies of each modality in tumor and nodal assessment in patients with T3/4 tumors receiving neoadjuvant chemotherapy were compared. METHODS-45 patients of a prospective clinical trial studying T3-T4M0 tumors were included. Patients received neoadjuvant chemotherapy: docetaxel/carboplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 20 publications
0
42
0
1
Order By: Relevance
“…of the extent of residual viable tumor [20][21][22][23]. In addition, preliminary results with bevacizumab in the neoadjuvant setting show that DCE-MRI is a suitable tool for evaluating renormalization of vasculature as a response to antiangiogenic therapy [24].…”
Section: Breast Vascular Maps and Dynamic Contrast-enhanced Mrimentioning
confidence: 99%
“…of the extent of residual viable tumor [20][21][22][23]. In addition, preliminary results with bevacizumab in the neoadjuvant setting show that DCE-MRI is a suitable tool for evaluating renormalization of vasculature as a response to antiangiogenic therapy [24].…”
Section: Breast Vascular Maps and Dynamic Contrast-enhanced Mrimentioning
confidence: 99%
“…Physical examination of the tumor remains the gold standard for assessing tumor size and the patient's suitability to receive neoadjuvant chemotherapy. 22 Survival-based endpoints are the most important endpoints when assessing the benefit of any therapy. However, accurately assessing the tumor response to neoadjuvant therapy also is critical.…”
Section: Evaluating the Efficacy Of Neoadjuvant Therapymentioning
confidence: 99%
“…Compared with pCR, assessment of cCR by clinical examination or mammography may overestimate the response to neoadjuvant therapy, with cCR rates usually higher than pCR rates (unpublished data). 22,23 Physical examination of the axillary lymph nodes is another useful technique that can be used for disease staging in patients who receive neoadjuvant therapy, although the use of positron-emission tomography (PET) for the assessment of metastases to the lymph nodes is increasing. A prospective clinical study of patients with T3 or T4M0 breast tumors (N ¼ 45) indicated that both physical examination and PET had high specificity but low sensitivity, correctly predicting pathologically positive lymph nodes, but not negative lymph nodes, after neoadjuvant therapy.…”
Section: Evaluating the Efficacy Of Neoadjuvant Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of palpation diagnoses depend on the examiner's experience, the size and location of the affected lymph node, and other factors. Prati et al (2009) reported that the accuracy of lymph node metastasis diagnoses by clinical palpation was 65% (sensitivity 74%, specificity 56%). Chae et al (2009) reported lymph node metastasis diagnoses using imaging diagnostics with 77.8%, 76.9%, and 73.2% accuracy and 51.5%, 33.3%, and 48.5% sensitivity by ultrasound, breast X-ray mammography, and positron emission tomography/computed tomography, respectively.…”
mentioning
confidence: 99%